(untitled) (Research, Society and Development, 2020)
The present work sought to analyze the phenomenon of multiparenthood or multiparenthood as a concretizing instrument of the rights and guarantees of children and adolescents, addressing the jurisprudential and doctrinal plans, raising positions of the Superior Court of Justice and understandings of the most varied authors. The general concepts of the family were dealt with here, showing that its current definition is very comprehensive and abstract, as well as it was written about the principles of Family Law that are, to some extent, related to the theme addressed here. In methodological terms, the deductive method was used, starting with a general and abstract analysis of the institutes of the family and of multiparenthood or multiparenthood, until arriving at a concrete and specific analysis, in the sense that the possibility of a child or adolescent having more than one father or more than one mother constitutes a right enshrined by the Brazilian legal system, although it does not have express provision in this sense. Finally, it was concluded that multiparenthood or multiparenthood has been gaining strength within the jurisprudence and doctrine of the homelands, in view of the very predominance, in certain cases, of emotional ties over the biological, adding that, although it is the right of the child and adolescent, this possibility should be applied with consideration, since it can cause injustices in the practical or material harvest, and should be analyzed on a case by case basis.